2009
DOI: 10.1159/000187719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Alveolar Ventilation on Isoflurane Arterial Blood Concentration and Its Uptake into the Human Body

Abstract: We investigated whether minute alveolar ventilation affects isoflurane concentration in arterial blood and uptake of isoflurane into the body. Thirty female patients scheduled to undergo elective gynecological surgery were randomly assigned to one of three groups: i.e. hyperventilation, normal ventilation and hypoventilation. Inspiratory (CIiso) and end-tidal (CEiso) concentrations of isoflurane were measured by infrared analysis, and arterial blood isoflurane concentration (Aiso) was analyzed by gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our previous study demonstrated that the application of increased alveolar ventilation led to elevated arterial blood isoflurane concentrations at the time of the initial administration of isoflurane and therefore resulted in its accelerated uptake into the body (6). Similarly, Enekvist et al demonstrated that ventilation with larger tidal volumes under isocapnia increased the rate of the rise in the arterial blood concentrations of sevoflurane compared with the normal tidal volumes (7).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that the application of increased alveolar ventilation led to elevated arterial blood isoflurane concentrations at the time of the initial administration of isoflurane and therefore resulted in its accelerated uptake into the body (6). Similarly, Enekvist et al demonstrated that ventilation with larger tidal volumes under isocapnia increased the rate of the rise in the arterial blood concentrations of sevoflurane compared with the normal tidal volumes (7).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of uptake of inhaled anesthetics depends on the alveolar concentration and ventilation 22-25 , blood solubility 5 and cardiac output 22 . Similarly, sevoflurane washout commences from the brain and body via the circulating blood into the alveolar space during elimination, allowing the lungs to ventilate it into the air.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Isoflurane in each blood sample was converted to the corresponding concentration, based on gas chromatographic measurements and blood-gas partition coefficient of isoflurane (λ) measured in each patient.…”
Section: Methodsmentioning
confidence: 99%